Conjunto de bases Gaussianas Universal para Átomos de K até Kr - Pansini, Fernando Néspoli Nassar (2013)
A small sized Universal Gaussian Basis Set for the atoms from K to Kr is presented. This set has been built from a single sequence containing 20 exponents generated from the DZP [1, 2, 3] basis sets. The Gaussians functions of all symmetries of each atom are extracted from the single sequence. These functions were chosen according to their in uence on total Hartree-Fock energy. For each studied atom a segmented contraction scheme was proposed and, then, di use and polarization functions were added. The Universal set generated in this work showed to be competitive with another adapted basis set of similar size on calculations of equilibrium geometry, electric dipole moment, and polarizability of a sample of molecules.